HUBUNGAN ANTARA SPIRITUAL QUOTIENT MAHASISWA DENGAN HASIL BELAJAR STRATEGI PEMBELAJARAN KIMIA YANG TERINTEGRASI DENGAN NILAI-NILAI ISLAM - Miterianifa Miterianifa (POTENSIA: Jurnal Kependidikan Islam, 2015)
This study aims to determine whether there is a relationship student Spiritual Quotient (X) with learning outcomes of chemistry learning strategy subjectsthat integrates with Islamic values (Y). This study used survey method with correlation analysis technique. This study is a populationstudy with total subjects of 29 responden.Data collection techniques by using questionnaires for spiritual variable quotient (X), and the test methods to collect data for variable of learning outcomes chemistry learning strategy that integrates with Islamic values (Y). The research data were analyzed using product moment correlation analysis techniques to test the hypothesis. The hypothesis testing showed that there is a positive correlation between student spiritual quotient with learning outcomes of chemistry learning strategy subjects that integrates with Islamic values, as indicated by the correlation coefficient between Xvariables and Y (rh = 0.77), both with a significance level 5% = 0.374, and a significance level of 1% = 0,478. So the analysis mentioned r0 greater than rt so the hypothesesare accepted and significant. Based on the results of the study, expected to be material information and input for Study Program of Chemical Education and Faculty of Education and Teacher Training, in particular for the Chairman of the Study Program, lecturers and students in order to always improve spiritualquotient potential students.